Você está na página 1de 13
2 ◦

2

x 2 + y 2 = k k x 2 + y 2 = 100

x 2 +y 2 = k k

x 2 + y 2 = 100

y

= 4 x

3

x = 3, y = 4

 

3 2 + 4 2 = 25 · (25

= 100)

25 = 5,

100 = 10

10 ÷ 5 = 2

2 × 3 = 6 2 × 4 = 8.
2 × 3 = 6 2 × 4 = 8.

x 2 x = 870 x (0, 5 × 0, 5 = 0, 25) 870 (870, 25 = (29, 5) 2 ) 1 (30)

0 , 25) 870 (870 , 25 = (29 , 5) 2 ) 1 (30) p

p q

x 2 px + q 2 = 0

0 , 25) 870 (870 , 25 = (29 , 5) 2 ) 1 (30) p

AB P E AB = p P E = q q < p 2 AB
AB P E AB = p P E = q q <
p
2
AB Q AQ + QB = p AQ · QB = q 2
E p AB
2

Q

q 2 = PB 2 PQ 2 = (P B P Q) · (P B + P Q) = QB · AQ.

r = AQ s = BQ

p = r + s q 2 =

x 2 3x + 1 = 0. p = 3 q

EQ =

PB =

r · s

=

1

3

2

P Q = 5

2

P E

=

q

=

1

s

=

AQ =

AP + P Q

=

3 + 5 .

2

2

r

= QB

=

AB AQ

=

3 3 + 5

2

r

= 3 + 5

2

x 2 px q 2 = 0

= 3 + √ 5 2 x 2 − px − q 2 = 0 AB

AB BE AB = p BE = q

Q AQ + QB = p AQ · QB = q 2 P E = P Q P AB q 2 + PB 2 = PE 2 = PQ 2

q 2 = PQ 2 PB 2 =

(P Q P B) · (P Q + P B) = QB · (P Q + P A) = QB · AQ.

r = AQ s = QB p = r s r · (s) = rs = QB · AQ = q 2 r s x 2 13x 9 = 0

AP =

PB =

p = 13 q = 3

13

BE

2

=

q

=

3

P E = 205

2

13 + √ 205 P E = P Q = P B + BQ =
13
+ √ 205
P
E
=
P Q =
P B + BQ
=
P B − QB
s =
QB
=
P B − P E
=
2
2
= 13 + √ 205
s
.
r
=
AQ
= AB + BQ
=
AB − QB
=
13 − 13 + √ 205
2
2
= 13 − √ 205
r
.

2

AB X AB XB AX AB AX a x a x a(a x) = x 2

ABCD AB

E DA

F DA EF = EB

AF BC

X AB

AE = 1 2 AD = 1

EF = EB AF BC X AB AE = 1 2 AD = 1 2 a.

2 a. ABE EB = a 2 + a 2 = a 5

2

2

a 5

2

a(1 + 5)

2

x = AX = AF

a(a x) = x 2 , AX.

= EF EA = EB EA =

a

2

=

5) 2 x = AX = AF a ( a − x ) = x 2

˙ ˙ y a v 1 y a ˙ 10 x 2 − 10 x

˙

˙

ya v 1 ya

˙

10

x 2 10x = 9

ru 9

9

36 + (10) 2 = 64

(9) · 4 = 36

64 = 8 8 (10) = 18 18 : (2 × 1) = 9

9. ˙ ya ka 7 bha k(a) 12 ru 8 ya v 3 ya 10
9.
˙
ya ka 7 bha k(a) 12 ru 8
ya v 3 ya 10
7xy + √ 12 − 8 =
= 3x 2 + 10x

x 2 = 1 + py 2

5 x 3 2 + 1 = x x 2 55 = 250

1

8 /9

ya v 2

2x 2

ya 1

2x 2

2

= x

ya v

16

9

16

9

x 2

ya v 2

x + 16 x 2 + 2 = 2x 2

9

ya v 18 ya 0 ru 0 ya v 16 ya 9 ru 18 9x
ya v 18 ya 0 ru 0
ya v 16 ya 9 ru 18
9x + 16x 2 + 18
= 18x 2
⇐⇒
9 9
18x 2 = 16x 2 + 9x + 18
ya v 2 ya 9 ru 0
ya v 0 ya ru 18
18x 2 − 16x 2 − 9x
16x 2 + 9x + 18 − 16x 2 − 9x
2x 2 − 9x
=
=
18
ya
x = 6
ya v 2 72
2x 2 = 2 · 6 2 = 72

− 9x 16x 2 + 9x + 18 − 16x 2 − 9x 2x 2 −

x 2 + 12 x = 64 . x         x  

x 2 + 12x = 64.

x

       

x

       

     

 

AB = BC = x AH = CF = 6. ABCD A q = x 2 HKBA BGF C A r = 6x. x 2 + 6x + 6x = x 2 + 12x. HEF D KEGB, A q = 36. HEF D

(x + 6) 2 = x 2 + 12x + 36 = 64 + 36 = 100,

x = 4.

x 2 + 252 x − 5292 = 0 x = 19 19 20 y

x 2 + 252x 5292 = 0 x = 19 19 20

y

y 2 y y =

0 1

x 19 y 2 + 290y

=

=

143

y

143

291

143

291 = 19, 49

x x = 19 +

z 0, 66

z =

98 = 0, 0022 2

= x 19, 49 z z 2 + 290, 98z = 0, 66

291,

19, 49226

z z 2 + 290 , 98 z = 0 , 66 291 , 19 ,

x 2 + 2ax = b

x + a = u

u 2 = x 2 + 2ax + a 2

 

x 2 + 2ax = b, u 2 = b + a 2

(x + a) 2 = u 2 =

b + a 2

x = b + a 2 a.

ax 2 + bx + c = 0,

ax 2 + bx + c = 0, a(u + z) 2 + b(u + z) + c = 0, au 2 + (2az + b)u + (az 2 + bz + c) = 0.

x = u + z

2az + b = 0, z = −b 2a .
2az + b = 0, z = −b
2a .

z = b 2a

au 2 + (2az + b)u + (az 2 + bz + c) = 0,

au 2 +

b

2

4a

2

2a + c

b

=

0,

au 2

=

b

2

2a

4a c = b 2 4ac

b

2

4a

,

± b 2 4ac

4a

u

=

z = b 2a

u = ± b 2 4ac

4a

x = b 2a

± b 2 4ac

4a

, x =

b ± b 2 4ac

2a

.

x

= u + z,

± √ b 2 − 4 a c 2 a . x = u + z,

x 2 = bx + c 2 x 2 = c 2 bx x 2 = bx c 2 b c x 2 = bx + c 2

LM c L NL

 

b

b

2 LM N

2

M N, O P.

b/2
b/2
OM MLN OM = x x − − OM 2 2 = b b 2

OM MLN OM = x

x

OM

2 2 =

b

b

2 2

+ c 2

x 2 bx = c 2

x 2 bx + c = 0 A = (0, 1) B = (b, c) AB x

c B = (b, c) A = (0, 1) M N b
c
B = (b, c)
A = (0, 1)
M
N
b

x 2 2 + y c + 1

b

2

2 =

b 2 + c + 1

2

2

1 2

y = 0, x 2 bx = c.

2 ◦